Applying the Theory of Planned Behavior in Examining the Intention to Improve Corporate Tax Compliance Through Compensation and Counterproductive Work Behavior - Erwin Harinurdin; Karin Amelia Safitri; Ronny Kountur (SAGE Open)
The interests of the agent (manager) are not always aligned with the interests of the principal. It is possible that the agent will act for himself and not in the best interest of the principal. In deciding the intention to take aggressive tax action, managers will consider the advantages and disadvantages of their actions. One way to limit counterproductive manager behavior is that the principal will pay compensation costs in the form of incentives. This research examines the compliance behavior of taxpayers represented by company managers. The main idea is to analyze various factors that shape taxpayer behavior regarding compensation in tax compliance. This research is based on a survey of managers at companies registered at the Central Tax Service Office in Bandung, West Java. Primary data was analyzed using Structural Equation Modeling (SEM). The research results show empirical evidence that company managers’ intentions toward tax compliance are supported by perception of control behavior and compensation. Counterproductive work behavior mediated by job satisfaction also supports tax compliance. Managers’ behavior toward the interests of utility principals is influenced by the compensation provided and reduces counterproductive work behavior. So that agency conflicts can be reduced and avoided.